Diversity of bivalves in mangrove forest, Tok Bali Kelantan, Malaysia - Kassim, Zaleha; Ahmad, Zuhairi; Ismail, Norshida (Zibeline International Publishing, 2018)
A study on the diversity and some ecological aspects that related to the abundance of infaunal bivalve species was done at Tok Bali mangrove, Kelantan, Malaysia. Samples and data collection was conducted during three different seasonal periods, on dry season (July), pre-monsoon (September) and monsoon (December) in the year 2015. Sampling stations were chosen in four mangrove forests which were encompassed with Rhizophora spp., Avicennia spp., Nypa fruticans and Mixed Mangrove. A collection of bivalve samples and sediment samples were done within 0.25 m2 quadrates and measurement of physico-chemical parameters were conducted using Hydrolab Quanta. Temperature, salinity and pH showed the normal mangrove value and decreased during monsoon, while dissolved oxygen show increasing during monsoon. Mean of grain size (ø) value ranged from 1.9 to 2.66 indicated that the sediment is fine sand. Mean TOM ranged from 0.67-1.45 g/g. A total of five (5) species of infaunal bivalves were observed, which were Polymesoda expansa, Marcia japonica, Gari ambigua, Pillsbryoconcha exilis and Donax faba. Diversity index H’ ranges from 0.72-1.27 and evenness index E’ ranged from 0.53-0.95 and richness index varied from 0.42-0.78. ANOVA tests showed that there were no significant differences for all biodiversity indices during dry, pre-monsoon and monsoon season (P>0.05). The results showed that the low biodiversity of infaunal bivalves in the mangroves of Tok Bali. They could be more affected by the spatial factors rather than the monsoon. Long-term data collection is suggested to determine the seasonal pattern of their biodiversity and contribution to the mangrove ecosystem in the area.